Penerapan Target Costing, Cost-Volume-Profit Dan Manajemen Persediaan Economic Order Quantity Untuk Efisiensi Biaya Produksi Dan Perencanaan Laba Pada UD. Karya Pala Kota Kediri - Fitria Nurul Izza; Marhaendra Kusuma; Miladiah Kusumaningarti (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2023)
The study objectives to recognize the utility of Target Costing, Cost-Volume-Profit and Economic Order Quantity inventory management for production cost efficiency and profit planning. The data analysis technique used in this research is descriptive and the method used in the target costing, cost-volume-profit and economic order quantity inventory management. The data source used in this research is primary data. This research was conducted at UD.Karya Pala which is located in Ds. Banjarmlati Kec. Mojokerto Kediri City. The results of the discussion show that the application of the target costing method helps obtained lower total production costs than before but with higher profits. The BEP value obtained shows has been able to generate profits from the production of fried soybeans because the amount of production per month is far above the break-even-point. Based on the EOQ calculation carried out, the estimated order quantity makes it easier for UD. Karya Pala optimizes warehouse usage and reduces the occurrence of excess or shortage of raw materials. The conclusion that can be drawn from this research is that it will be more profitable if the company uses the three methods because it can help to efficiency production costs and profit planning.